1975
DOI: 10.3171/jns.1975.42.2.0144
|View full text |Cite
|
Sign up to set email alerts
|

Local spinal cord blood flow in experimental traumatic myelopathy

Abstract: Focal blood flow was measured in the lateral funiculus and center of the spinal cord in the rhesus monkey both before and after a 600 gm-cm injury at T-10. Measurements made by the hydrogen clearance technique showed that blood flow in the lateral funiculus more than doubled within 4 hours after injury, returned to normal by 8 hours, and remained in the normal range for 24 hours. At no time was a hypoperfusion in the lateral funiculus present. Blood flow in the center of the spinal cord, at the level of the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(29 citation statements)
references
References 8 publications
2
24
2
1
Order By: Relevance
“…Kobrine and associates' experimental study 46 investigating the impact of severe (600 g/cm) injury in monkeys opposes this theory. In the lateral white matter SCBF more than doubled (p < 0.01) within 1 hour of injury and returned to normal after 8 hours.…”
Section: Gray To White Injurymentioning
confidence: 85%
See 1 more Smart Citation
“…Kobrine and associates' experimental study 46 investigating the impact of severe (600 g/cm) injury in monkeys opposes this theory. In the lateral white matter SCBF more than doubled (p < 0.01) within 1 hour of injury and returned to normal after 8 hours.…”
Section: Gray To White Injurymentioning
confidence: 85%
“…70 The increase in SCBF in white matter after injury also could be a response to increased metabolic demand or loss of autoregulation and subsequent vascular dilation as a direct result of trauma. 46 A documented increase in histamine levels at the site of trauma, known to cause vascular dilation by weakening vascular tone, also explains the increased blood flow in white matter.…”
mentioning
confidence: 99%
“…Subsequently, after studies of the physiopathology, we saw that axial tensions and angulations were much more important factors. (Breig, 1960;Holdsworth, 1963;Kobrine, 1975;Torre, 1981). For these reasons, laminectomy has been relegated to a second…”
Section: Discussionmentioning
confidence: 99%
“…Based on the follow ing protocol we decided on surgical or non-surgical treatment for the spinal cord injury (Green, 1981;Harris, 1978;Holdsworth, 1975;Kobrine, 1975;Masini and Walters, 1986). …”
Section: Clinical Materials and Treatmentmentioning
confidence: 99%
“…It was shown that H, and Hj antagonists, administered systemically together, prevented hyperemia that develops in tissue adjacent to an injured segment of spinal cord. 17 Clasen et al" tried unsuccessfully to reduce the amount of edema produced by a standardized cryogenically induced cerebral injury with a combination of a glucocorticosteroid and the H t antagonist chlorpheniramine. Outside of the central nervous system, HA increases vascular permeability"' M that leads to plasma exudation and the accumulation of interstitial edema.…”
Section: S3mentioning
confidence: 99%